Radiofrequency In Situ Fenestration for Aortic Arch Vessels During Thoracic Endovascular Repair. (February 2015) - Tse, Leonard W.; Lindsay, Thomas F.; Roche-Nagle, Graham; Oreopoulos, George D.; Ouzounian, Maral; Tan, Kong Teng
Purpose: To report the first clinical application of a novel technique using radiofrequency puncture to create retrograde in situ fenestrations during thoracic endovascular aortic repair (TEVAR).Methods: Between June 2011 and December 2013, 40 TEVAR procedures were performed in our facility, including 10 cases in which in situ fenestration was planned. Two thoracic stent-graft models were deployed: the Valiant (n=5) and the Zenith TX2 (n=5). A 0.035-inch PowerWire radiofrequency guidewire delivered from a brachial approach was used to fenestrate the grafts covering a left subclavian artery (LSA) in 9 cases and a left common carotid artery in one. The fenestrations were serially dilated to 6 mm, and self-expanding Advanta V12 covered stents were positioned in the target arteries.Results: Technical success was achieved in 6 of the 10 planned cases. Of the remaining 4 cases, stent-grafts were deployed in zone 3 in 2 cases (one received a chimney to the LSA). Another stent-graft was deployed in zone 2 without endoleak after fenestration was abandoned (the LSA had good filling via the vertebral artery). In the last case, the fenestration was unsuccessful in double-layered (proximal extension overlap) stent-grafts; a carotid-axillary bypass was required. There were no fenestration-related complications, but overall surgical complications included a case of paraparesis that resolved following spinal drainage and a death from a preexisting aortoesophageal fistula. There were no postoperative strokes. All fenestrations remained patent, and there were no endoleaks at a mean 12-month follow-up (range 1–33).Conclusion: Radiofrequency puncture is a viable alternative to needle or laser punctures for in situ fenestration during TEVAR. Early clinical results suggest technical feasibility and acceptable early outcomes.